Increased granzyme B production from peripheral blood mononuclear cells in patients with acute coronary syndrome. Issue 3 (25th June 2007) - Tsuru, R; Kondo, H; Hojo, Y; Gama, M; Mizuno, O; Katsuki, T; Shimada, K; Kikuchi, M; Yashiro, T
Abstract : Objectives: To clarify the role of granzyme B in acute coronary syndrome. Design and Setting: Granzyme B is a member of the serine esterase family released from cytotoxic lymphocytes and plays an important role in cellular apoptosis by activating intracellular caspases. Granzyme B expression was compared between patients with stable and unstable angina pectoris (UAP). Patients: 173 patients with coronary artery disease (CAD) were enrolled. 84 patients were found to have stable angina pectoris (SAP) and 89 patients to have UAP. Methods: Peripheral blood was drawn from the patients. Peripheral blood mononuclear cells (PBMCs) isolated by gradient centrifugation were cultured at a density of 2×106 cells/ml for 24 hours. The supernatants were collected 24 hours after incubation and the granzyme B level was measured by enzyme-linked immunosorbent assay. Polychromic flow cytometric analysis was performed to evaluate the expression of granzyme B in the cells. Results: Granzyme B production from PBMCs of UAP patients was significantly higher than from those of patients with SAP (39.1 (SEM 6.6) versus 17.0 (SEM 1.8) pg/ml, p<0.05). Granzyme B production from PBMCs increased with the increasing TIMI risk score in UAP patients. The percentage of granzyme B-positive lymphocytes to CD3-positive lymphocytes in UAP patients was significantly higher than in SAP (32.1% (SEM 1.6%) versus 18.4% (SEM 0.9%), p<0.01). Conclusions: These results suggest that granzyme B might play an important role in triggering acute coronary events by inducing apoptosis and the degradation of atherosclerotic coronary plaques.